Highly bioactive iridium metal-complex alleviates spinal cord injury via ROS scavenging and inflammation reduction. (May 2022) - Ji, Zhi-Sheng; Gao, Gui-Bin; Ma, Yan-Ming; Luo, Jian-Xian; Zhang, Guo-Wei; Yang, Hua; Li, Nan; He, Qing-Yu; Lin, Hong-Sheng
Abstract: Generation of a promising antioxidative reagent with superior biocompatibility is urgently needed to remedy spinal cord injuries (SCI), repair the damaged neurons and restrain the secondary injuries caused by inflammation-induced oxidative stress. Inhibitory elements in the injury sites and necessitous inherent neural regeneration ability were major challenges for functional recovery after spinal cord injuries. We here developed a highly bioactive iridium complex (IrFPHtz) with enhanced antioxidative activities and improved SCI therapeutic efficacy. Both in vivo and in vitro, IrFPHtz has exhibited neuroprotective and anti-inflammatory properties. Mechanically, IrFPHtz directly targets SOD1 and upregulates the expression of SOD1 to eliminate the excess Reactive Oxygen Species (ROS) production induced by SCI, and thus protecting neuron cells from further damage. As a result, IrFPHtz safeguarded the neurons and myelin sheaths against trauma, lessened glial scar conformations and facilitated the repair of neurons and long axon expansion in the glial scar. Furthermore, IrFPHtz significantly ameliorated the behavioral functions of SCI mice and promoted a satisfactory curative effect. Therefore, this study sheds light on a novel method for SCI treatment using IrFPHtz as a potential drug and implicates the clinical significance of metal complexes in diseases featuring with upregulated ROS species. Graphical abstract: Herein a metal complex IrFPHtz with enhanced antioxidative activities and acted as an efficient ROS scavenger to protect neuron against harmful oxidative stress. IrFPHtz directly interacts with SOD1 to exact its biological function of eliminating superoxide radicals toxic to biological systems. As a result of its excellent anti-inflammatory and ROS-scavenging effects, IrFPHtz has been considered as a potential therapeutic drug for treating spinal cord injuries. Image 1 Highlights: A metal complex IrFPHtz with enhanced antioxidative activities. IrFPHtz acted as an efficient ROS scavenger to protect neuron. IrFPHtz directly interacts with SOD1 to exact eliminating superoxide radicals toxic. IrFPHtz significantly promoted a satisfactory curative effect of SCI mice.